Evaluation of in vitro anti-inflammatory effects of the remaining water subextract of Cistus laurifolius leaves - Atay, İrem; İlter, Ayça Zeynep; Bagatur, Yeşim; Telci, Dilek; Kırmızbekmez, Hasan; Yeşilada, Erdem (Georg Thieme Verlag, 2015)
Cistus laurifolius L. (Cistaceae) is known as 'laden' in Anatolia and the leaves of the plant are used against rheumatismal diseases traditionally [1]. The ethanol extract of the leaves were submitted to solvent-solvent extractions and n-hexane, chloroform, ethyl acetate, n-butanol, remaining water subextracts were obtained. The extract and subextracts were investigated for their inhibitory effects on Nuclear Factor kappa B (NF-?B) transcrption factor on lipopolysaccharide induced Raw 264.7 macrophages. Only remaining water subextract exerted 20% inhibition. The subextract was fractionated by chromatographic methods but the fractions were found to be not effective. Thus, remaining water subextract was directed for further in vitro anti-inflammatory investigations. The effects on nitric oxide (NO), prostaglandine E2 (PGE2), tumor necrosis factor (TNF?) and interleukins (IL-1?, IL-1?, IL-2, IL-6) were studied by Griess and ELISA. The effects on iNOS and COX-2 protein levels and the phosphorylation levels of mitogen activated protein kinases (ERK1/2, JNK, p38) and I kappa B alpha (I?B?) were examined by Western Blot method. The subextract was applied to Raw 264.7 macrophage cells at 25, 50 and 100 µg/mL concentrations and it provided up to 57% decrease of NO production and up to 55% decrease of PGE2 production of cells. The iNOS and COX-2 protein levels were decreased accordingly. The subextract exerted inhibitory effect on TNF? (37%). This subextract inhibited the phosphorylation of I?B? at 50 and 100 µg/mL concentrations while JNK phosphorylation was concentration-dependently inhibited.
63rd International Congress and Annual Meeting of the Society-for-Medicinal-Plant-and-Natural-Product-Research (GA) -- August 23-27, 2015 -- Budapest, Hungary
WOS: 000367558100415
Keywords: Evaluation; Subextract; Cistus